A Comprehensive Carbon Footprint Monitoring Framework for Sustainable Apparel Manufacturing (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study proposes the design, implementation, and evaluation of a software-based carbon footprint monitoring system developed specifically for the apparel manufacturing industry. As one of the major contributors to global greenhouse gas (GHG) emissions, the sector faces increasing pressure to monitor and reduce its environmental impact arising from energy-intensive activities such as fabric production, dyeing, garment manufacturing, and transportation. Existing carbon monitoring approaches often depend on hardware-based systems that provide historical data but offer limited support for real-time intervention and decision-making. The proposed platform consolidates production information, energy consumption records, material utilization, and logistics data into a unified digital system. Using standardized emission factors, it continuously calculates carbon dioxide (CO₂) emissions and provides real-time visibility into environmental performance. This enables manufacturers to identify emission hotspots, implement corrective actions promptly, and improve overall sustainability outcomes. The study also examines market readiness and adoption trends for digital carbon monitoring solutions. Growing environmental regulations, sustainability reporting requirements, and increasing consumer demand for eco-friendly products have accelerated the need for effective carbon management tools. Major apparel-producing countries, including Bangladesh and China, are increasingly adopting such technologies to meet international trade expectations and sustainability commitments. Evidence from industry case studies indicates that digital monitoring systems contribute to measurable reductions in energy use and carbon emissions while supporting operational efficiency. Furthermore, the research highlights the influence of carbon taxation policies, sustainability standards, and financial incentives such as subsidies and green financing in promoting technology adoption. The findings demonstrate that real-time software-based carbon monitoring systems can generate both environmental and economic benefits, helping apparel manufacturers achieve regulatory compliance, improve competitiveness, and advance long-term sustainability goals.